Визначення ймовірності відповідності засобів вимірювальної техніки метрологічним вимогам - Захаров, І. П.; Неєжмаков, П. І.; Боцюра, О. А. (ННЦ "Інститут метрології", 2018)
The requirements of ISO/IEC 17025:2017, which affect the indication of the information about measurement uncertainty and statement of compliance with the requirements or specifications in the calibration certificates of measuring instruments (MIs), are analyzed. The provisions of European and International reference documents concerning the conformity assess- ment of the investigated object with the requirements of the technical documentation are considered. It has been shown that in some cases the result of calibration of a MI in its compliance assessment with metrological requirements may be in the uncertainty zone. In these situations, in accordance with JCGM 106:2012 and OIML G 19:2017, it is necessary to assess the probability of compliance of the MI with the requirements of the technical documentation in order for the customer to determine the risk of further use of this MI in production practice. Expressions for assessing the probability of compliance of MI with metrological requirements for different distribution laws of the measurand are presented. The diagram, which allows carrying out operative control of probability of compliance of calibrated MI, is constructed. An algorithm for applying the Monte Carlo method to calculate the probability of a MI correspondence based on the uncertainty budget obtained during its calibration for any law of the distribution of the measurand is developed. Examples for calculating the probability of compliance of calibrated measuring instruments with the metrological requirements established in the technical documentation are given.
Determination of the probability of compliance of the measuring instruments with the metrological requirements
Keywords: conformity assessment; uncertainty of measurement; probability of compliance; verification; calibration